Solid-state compounds of 2-chlorobenzylidenepyruvate with some bivalent metal ions - Synthesis, characterization and thermal behaviour - Bannach, G.; Siqueira, A. B.; Ionashiro, E. Y.; Rodrigues, E. C.; Ionashiro, Massao [UNESP] (Springer, 2007)
Solid-state M-2-Cl-BP, where M stands for Mn, Fe, Co, Ni, Cu, Zn and Pb and 2-Cl-BP is 2-chlorobenzylidenepyruvate, have been synthesized. Thermogravimetry and derivative thermogravimetry (TG/DTG), simultaneous thermogravimetry and differential thermal analysis (TG-DTA), X-ray powder diffractometry, infrared spectroscopy, elemental analysis, and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds.
Keywords: bivalent metals; 2-chlorobenzylidenepyruvate; coordination sites; thermal behaviour